TARI KOMPANIA: SEBAGAI MEDIA PENCEGAHAN DAN PENGOBATAN PENYAKIT DI DESA WASALABOSE KECAMATAN KULISUSU KABUPATEN BUTON UTARA - Nurliana Nurliana; Wa Ode Sifatu; La janu (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2018)
This study aims to determine the reasons Kompania dance as a media for the prevention and treatment of diseases among the people of Wasalabose Village. This study uses the ethnographic method with the technique of collecting data through observation and in-depth interviews. The data collection is a descriptive qualitative. The results of the study show that Kompania dance is a traditional dance which is carried out as an expression of gratitude and illustrates the victory in the war between the Kulisusu forces against the Company who had taken control of the Ambon area. Kompania dance is held twice a year during the celebration of Eid al-Fitr and Eid al-Adha and cannot be done on another day. The Kulisusu community in Wasalabose Village made Kompania dance as a means of preventing and treating diseases because there are sacred or magical powers in the dance which are believed to be able to prevent and treat various diseases. Generally, patients who come in rituals and ask for prayer so as to avoid various kinds of diseases kept away from disasters and given a long life. Compania dance has several functions, namely health functions, religious functions, functions of art (entertainment), economic functions and social functions. Keywords:Kompania dance, preventions, treatment, diseases